Regulation of Pancreatic microRNA-7 Expression. (17th May 2012) - Kredo-Russo, Sharon; Ness, Avital; Mandelbaum, Amitai D.; Walker, Michael D.; Hornstein, Eran
Abstract : Genome-encoded microRNAs (miRNAs) provide a posttranscriptional regulatory layer, which is important for pancreas development. Differentiation of endocrine cells is controlled by a network of pancreatic transcription factors including Ngn3 and NeuroD/Beta2. However, how specific miRNAs are intertwined into this transcriptional network is not well understood. Here, we characterize the regulation of microRNA-7 (miR-7) by endocrine-specific transcription factors. Our data reveal that three independent miR-7 genes are coexpressed in the pancreas. We have identified conserved blocks upstream of pre-miR-7a-2 and pre-miR-7b and demonstrated by functional assays that they possess promoter activity, which is increased by the expression of NeuroD/Beta2. These data suggest that the endocrine specificity of miR-7 expression is governed by transcriptional mechanisms and involves members of the pancreatic endocrine network of transcription factors.